Formulation and Evaluation of Dishwashing Soap Based on Eichhornia crassipes Activated Carbon as an Environmentally Friendly Cleanser - Nurrohimi, Erlin Dwi; Pramana, Arjuna; Idayanti, Rina; Husna, Marsha Azharia; Amelia, Lisa; Wirhanuddin, Wirhanuddin (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Eichhornia crassipes is an invasive aquatic plant found in tropical and subtropical waters that has high cellulose, lignin, and hemicellulose content, making it a potential raw material for activated carbon. The use of activated carbon in dishwashing soap can enhance cleaning power by absorbing oil, odors, and microscopic dirt. This study aims to formulate and evaluate a liquid dishwashing soap product containing carbon from water hyacinth as a natural cleaning agent. The water hyacinth samples used were dried stems, collected from local water bodies, and prepared by drying under sunlight to reduce moisture content. The stems were then subjected to carbonation at 600 °C for 60 minutes to produce biochar, followed by a comminution process using ball milling to produce fine activated carbon powder. The resulting carbon was formulated into a dishwashing soap base at a ratio of 1 mg per 100 mL of product. Product evaluations were conducted based on Indonesian National Standards (SNI) and yielded the following results: a pH value of 9.78 (SNI 8–10.8), foam stability of 90% (SNI 60–100%), viscosity of 206.11 cP (SNI 400–4000 cP), free alkali content of 0.104% (SNI <0.14%), and specific gravity of 1.045 g/mL (SNI 1.01–1.1 g/mL). The novelty of this study lies in the utilization of activated carbon derived from Eichhornia crassipes, which is formulated into liquid dishwashing soap and comprehensively evaluated based on national quality standards (SNI). This approach has rarely been reported in similar studies. The results demonstrate the potential of water hyacinth as an alternative active ingredient in the development of sustainable household cleaning products.